State of the Art in Development of Heat Exchanger Geometry Optimization and; Materials; Vol. 16, iss. 13 - Kudiyarov V. N. Victor Nikolaevich; Elman R. R. Roman Romanovich; Pushilina N. S. Natalia Sergeevna; Kurdyumov N. Nikita (2023, 2023)
Title screen